New methods in diagnosis and therapyTranscatheter closure of patent foramen ovale using the internal jugular venous approach - Węglarz, Przemysław; Konarska-Kuszewska, Ewa; Zębik, Tadeusz; Kuszewski, Piotr; Drzewiecka-Gerber, Agnieszka; Motyka, Marek; Ludyga, Tomasz; Bajor, Grzegorz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Transcatheter closure of patent foramen ovale is routinely performed using the transfemoral approach, which is safe and technically easy. Our case represents the rare situation where the procedure needs to be performed using the right internal jugular venous approach. According to our best knowledge this is the first report of a patent foramen ovale closure procedure with access through the internal jugular with necessity to advance the guide wire and transseptal sheath into the left ventricle. Developing alternative techniques of transcatheter patent foramen ovale closure seems to be especially important in rare cases where transfemoral access is unavailable.